Relationship between appearance-related social media consciousness and beliefs about obese persons among physical education teacher candidates - Canan Sayın Temur (PLoS ONE, 2026)
Objective This study examined whether physical education teacher candidates’ appearance-related social media consciousness and beliefs about obese persons differed by teacher candidates’ gender and years of study and whether there was a relationship between these two factors. Method A correlational research design was employed in the study. The study involved 153 physical education teacher candidates. Data were collected using the Demographic Information Form, the Appearance-Related Social Media Consciousness Scale and, the Beliefs about Obese Persons Scale. The data were analyzed using the Mann-Whitney U, Kruskal-Wallis, and Spearman’s rank correlation tests. Results The results showed that there was no statistically significant difference between the level of appearance-related social media consciousness and the level of beliefs about obese persons between female and male physical education teacher candidates. In terms of years of study, the level of appearance-related social media consciousness was lower among those in their 2 nd and 3 rd years than among those in their 4 th year, and the level of attitudes towards obese persons was lower in the 3 rd year than in the 4 th year. The results further showed no correlation between the levels of appearance-related social media consciousness and attitudes towards obese persons among the physical education teacher candidates. Conclusion These findings highlight the importance of physical education teacher education programs actively addressing appearance-related social media consciousness and beliefs about obese persons, with the aim being to mitigate the emergence of weight-based stigma and foster more inclusive, informed attitudes.